Super‐size me: adipose tissue‐equivalent additions for anthropomorphic phantoms. (8th November 2014) - Fisher, Ryan F.; Hintenlang, David E.
Abstract : Physical anthropomorphic phantoms have been utilized for a variety of dosimetric studies across a range of procedures utilizing diagnostic imaging equipment. Unfortunately, these phantoms are often limited to a single reference size, which often may not be representative of the patient population at large. This work set out to develop an adipose tissue‐equivalent substitute material that could be used to create low cost physical additions for existing anthropomorphic phantoms. Using commercially available products, a methodology was developed to accomplish this, and an addition was built to create a 90th percentile by weight phantom from an existing 50th percentile model. This methodology can easily be used to expand the utility of existing anthropomorphic phantoms in order to better represent patients of various body morphologies, and investigate the effects of patient size in diagnostic procedures. PACS numbers: 87.53.Bn, 87.57.qh